Computer Based Multi Media Presentaion - An Emerging Instructional System for Technical Education - Soni, S. K. (Journal of Engineering Education Transformations, 1997)
Computer Based Multi Media Presentation, as a means for disseminating information has become very common in the industry and commercial world. It has become all essential feature of industry/modern trade fare. The Multi Media Presentation Technology is the result of convergence of a variety of brief technologies based on computer, video, and audio engineering and imaging technologies. The basic infrastructure ill terms of hardware, software human-ware and use-ware is available in technical educational system. It is getting reinforced with time. It is time for the policy makers and managers of the policy makers and managers of technical education system to get acquainted with the potentials and possibilities of MMP packages, its implications and applications to enhance the quality of the graduates and technicians coming out of technical education system.